EVALUATION AND USER INTERFACE DESIGN IMPROVEMENT RECOMMENDATIONS OF THE IMMIGRATION SERVICE APPLICATION USING DESIGN THINKING - Hendarto, Alexander Ryan; Werdiningsih, Indah; Kartono, Kartono (PATTIMURA UNIVERSITY, 2024)
The M-Paspor application is an immigration service application. It is an application that is officially managed by the Directorate General of the Ministry of Law and Human Rights of the Republic of Indonesia. With this online service system, people who wish to apply for passports do not need to come to the office and stand in line to make passports, now they only need to access the Directorate General of Immigration's website or this mobile-based application to submit an application. This study aims to evaluate and provide recommendations for user interface improvements that can be proposed to improve the user experience of the M-Paspor application. This research used the design thinking method. Design thinking itself consists of five stages, namely empathy, define, idea, prototype, and test. Some of the problems in the user experience of the M-Paspor application are the confusing flow and interface, the loading process takes too long, the information guide is not informative, the display is boring and inconsistent. The user experience of the M-Paspor application has been tested with 15 respondents through five usability test task scenarios. The test results shown that the average aspect of effectiveness is 100%, the average aspect of efficiency is 0.133 goals/second with a range of 0.197 goals/second, and the average aspect of user satisfaction is 5.1 with a range of 2.4 (from a scale of 1 to 7).